Validation of the Sinhala version of the Montreal Cognitive Assessment in screening for dementia - Karunaratne, S.; Hanwella, Raveen; De Silva, V. (Ceylon Medical Journal, 2011)
Objectives: To validate the Sinhala version of the Montreal Cognitive Assessment (MoCA) scale in screening for dementia. Methods: The MoCA translation and cultural adaptation was carried using a combined qualitative and quantitative approach. Sample size was calculated to detect a targeted sensitivity of 85% and a specificity of 85%. Sample consisted of 49 participants diagnosed with dementia of the Alzheimer's type (AD) according to DSM-IV criteria and 49 normal controls (NC) aged ≥50 years. All subjects were administered the Mini Mental State Examination (MMSE) and MoCA Sinhala version (MoCA-S). Concurrent validity was assessed using Pearson correlation coefficients between the MoCA-S scores and MMSE scores. Criterion validity was assessed using receiver operating characteristic (ROC) analysis. Results: Mean MoCA scores between NC (26.71, SD 2.4) and AD group (16.78, SD 5.9) were significantly different (t=10.8, p<0.001). Cronbach's alpha of 0.818 indicated good internal consistency. Attention (digit span, sustained attention, and the serial 7 calculation task) had the highest discriminant ability followed by visuospatial skills (trail making, cube drawing and clock drawing). Naming had poor discriminant ability. There was a high, positive correlation between MoCA-S total scores and MMSE total scores. (r=0.907, p<0.001). The area under the ROC curve was 0.975 (95%CI 0.94-1.0) for the MoCA and 0.928 (95% CI 0.87-0.98) for MMSE. A cut-off value of 24 provided the best balance between sensitivity (98.0 7%) and specificity (79.6 %). Conclusion: MoCA-S is a valid and reliable instrument which can be used as a brief screening instrument for dementia in Sri Lanka.
Keywords: Montreal Cognitive Assessment; dementia; validation; Sinhala; scales